Molecular Diagnosis in Clinical Management and Diagnosis of Thyroid Cancer - Abbas, Hussein Saleh Hussein (Journal of Thyroid Cancer, 2024)
The prevalence of thyroid cancer is rapidly increasing worldwide, majorly due to overdiagnosis and overtreatment methods of differentiated thyroid cancer. The emergent and potent preclinical models, high-throughput molecular techniques, and genetic expression microarrays have delivered deeper insights into understanding the molecular features in oncogenesis. Thus, molecular markers have become a promising tool in managing thyroid cancer for differentiating benign and malignant tumors, prognosis, recurrence, and determination of novel therapeutic targets. In differentiated thyroid cancer, molecular markers are majorly utilized for guiding the development of indeterminate thyroid nodules on fine needle aspiration (FNA) histologies. Dissimilar to this, in advanced thyroid cancer, molecular markers permit targeted treatment of a modified signaling cascade. Determining causal mutation of targeted kinase receptors in advanced thyroid cancer can depict a promising treatment strategy with mutation-targeted tyrosine kinase inhibitors to reduce progression and eradicate mutation effects when conventional methods fail to manage. This review will focus on the molecular landscape and discuss the impact of molecular markers on the prognosis, treatment, and surveillance of differentiated and anaplastic thyroid cancer.
Keywords: molecular markers; thyroid cancer; tyrosine kinase inhibitors; thyroid nodules; targeted therapy